2008
DOI: 10.1109/tit.2008.928292
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Resilient Golay Complementary Waveforms

Abstract: We present a systematic way of constructing a Doppler resilient sequence of Golay complementary waveforms for radar, for which the composite ambiguity function maintains ideal shape at small Doppler shifts. The idea is to determine a sequence of Golay pairs that annihilates the low-order terms of the Taylor expansion of the composite ambiguity function. The Prouhet-Thue-Morse sequence plays a key role in the construction of Doppler resilient sequences of Golay pairs. We extend this construction to multiple dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
169
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(173 citation statements)
references
References 40 publications
3
169
0
1
Order By: Relevance
“…In this paper, we extend the result of [13]- [15] to construct pulse trains of Golay complementary waveforms, for which the range sidelobes of the ambiguity function vanish inside a desired Doppler interval away from zero. This is accomplished by coordinating the transmission of a Golay pair of phase coded waveforms in time according to the 1's and −1's in a …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this paper, we extend the result of [13]- [15] to construct pulse trains of Golay complementary waveforms, for which the range sidelobes of the ambiguity function vanish inside a desired Doppler interval away from zero. This is accomplished by coordinating the transmission of a Golay pair of phase coded waveforms in time according to the 1's and −1's in a …”
Section: Introductionmentioning
confidence: 91%
“…One way to accomplish this is to design the sequence P so that its spectrum S P (θ) has a high-order null at a Doppler frequency inside the desired interval. This idea has been explored in [13]- [15], where it is shown that the spectrum of a PTM sequence of length 2 M+1 has an M th-order null at θ = 0. Definition 3: [16], [17] The Prouhet-Thue-Morse (PTM) sequence P = (p k ) k≥0 over {−1, 1} is defined by the following recursions:…”
Section: Ptm Pulse Trains Of Golay Complementary Waveformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition: An ðM; K; NÞ sequence set S can be defined as an ðM; K; NÞ CCS if it satisfies [4,7,8,9]. In such a system, the received signal at the kth pulse can be expressed as…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed [7]- [9] that by proper sequencing of only two complementary waveforms across time it is possible to achieve an ambiguity response that is free of range sidelobes inside a desired Doppler interval. The complementary codes used are Golay complementary codes [10]- [12] invented Marcel Golay, which have the property that the sum of their autocorrelation functions is an impulse in delay.…”
Section: Introductionmentioning
confidence: 99%